Lead safety : a practical handbook for frontline supervisors and safety practitioners - Casey, Tristan William; Griffin, Mark A. (Boca Raton, FL : CRC Press, 2020)
"LEAD takes safety leadership in an exciting new direction, with practical tools, that will give organisation's the skills they need to make a difference in their safety program. The book provides a non-technical overview of safety leadership and outlines the core skills safety managers should demonstrate and practice to improve engagement, morale, trust, and motivation in the workplace"--
OCLC-licensed vendor bibliographic record.
Keywords: Industrial safety -- Management; Leadership; TECHNOLOGY / Industrial Health & Safety